Sources and transfers of cash income in the rural economy: The case of smallholder mixed farmers in the semi-arid zone of Mali - Debrah, S.K.; Sissoko, K. (International Livestock Centre for Africa, 1990)
Estimates the relative shares of crop livestock and non-farm income sources in total cash incomes of sample smallholder producers in the semi-arid zone of Mali and attempts to understand the mechanisms and motives of cash income transfers from one sector to the other. Describes the study area and the farming system of the sample, followed by an estimation of cash earnings from various sources in the 1987/88 farming season, and the various mechanisms by which earnings generated from a sector are transferred to other sectors in the rural economy. Ends with conclusions and policy implications based on the findings of the study.